(untitled) (Cardiovascular Journal, 2016)
A 52 year-old male patient of severe MS with mild MR with AF with a giant left atrium (LA size 70 mm) and history of CMC presented with symptoms. Giant left atrium is a condition characterized by huge enlargement of the left atrium with a diameter exceeding 65mm. It is most commonly associated with long standing rheumatic mitral valve disease. The patient underwent successful mitral valve replacement and removal of LA thrombus and discharged from hospital with advice Cardiovasc. j. 2016; 9(1): 73-74